Impact of Cytokine Expression in the Pre‐Implanted Donor Lung on the Development of Chronic Lung Allograft Dysfunction Subtypes. Issue 12 (24th October 2013) - Saito, T.; Takahashi, H.; Kaneda, H.; Binnie, M.; Azad, S.; Sato, M.; Waddell, T. K.; Cypel, M.; Liu, M.; Keshavjee, S.
Abstract The long‐term success of lung transplantation continues to be challenged by the development of chronic lung allograft dysfunction (CLAD). The purpose of this study was to investigate the relationship between cytokine expression levels in pre‐implanted donor lungs and the posttransplant development of CLAD and its subtypes, bronchiolitis obliterans syndrome (BOS) and restrictive allograft syndrome (RAS). Of 109 patients who underwent bilateral lung or heart–lung transplantation and survived for more than 3 months, 50 BOS, 21 RAS and 38 patients with No CLAD were identified by pulmonary function test results. Using donor lung tissue biopsies sampled from each patient, expression levels of IL‐6, IL‐1β, IL‐8, IL‐10, interferon‐γ and tumor necrosis factor‐α mRNA were measured. IL‐6 expression levels were significantly higher in pre‐implanted lungs of patients that ultimately developed BOS compared to RAS and No CLAD (p = 0.025 and 0.011, respectively). Cox regression analysis demonstrated an association between high IL‐6 expression levels and BOS development (hazard ratio = 4.98; 95% confidence interval = 2.42–10.2, p < 0.001). In conclusion, high IL‐6 mRNA expression levels in pre‐implanted donor lungs were associated with the development of BOS, not RAS. This association further supports the contention that early graft injury impacts on both late graft function and early graft function.